The Transfer of Subsidized Home Ownership Through Oper Credit Without Creditor's Knowledge in the Concept of Legal Certainty - Mulyadi, Hadi (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
This study aims to find out and analyze the transfer of subsidized housing ownership through credit transfer without the knowledge of the creditor in the concept of legal certainty and to know and analyze what are the causes and solutions to the transfer of subsidized housing through credit transfer. The research approach method used in this thesis is a sociological juridical legal research method. The specification of this research uses descriptive analysis. The type of data used in this study is primary data which includes the 1945 Constitution; Act No. 2 of 2014; Mortgage Act; Code of Civil law; The Criminal Code, as well as secondary data containing books and other supporting documents. Collecting research data using interview techniques and study of documents or library materials. The sale of a KPR house by the debtor cannot eliminate the debtor's obligation to pay off his debt to the Bank. Switching home loans without the knowledge of the bank as the creditor before the credit is paid off is an act that the debtor may not do, this is because the contents of the credit agreement bind the first party (Bank ) with the second party/credit recipient, namely the first debtor. If someone makes a house loan intentionally and without notifying the Bank as the creditor to sell or transfer it to another party, the action is classified as a